Occurrence and expression of p53 suppressor gene and c-Myc oncogene in dog eyelid tumors - Lopes, Rodrigo Antonio [UNESP]; Cardoso, Tereza Cristina [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Andrade, Alexandre Lima de [UNESP] (Wiley, 2010)
Purpose: To detect the occurrence and expression of the suppressor gene p53 and of the oncogene c-Myc in eyelid tumors of dogs using the PCR, RT-PCR, PCR-ELISA and RT-PCR-ELISA techniques. These genes have not been described in dog eyelid tumors before. Methods: Nine samples of eyelid or third eyelid epithelial tumors were obtained from the archives of the Department of Veterinary Pathology. Tumor diagnosis was confirmed by evaluation of hematoxylin-eosin stained sections, and immunohistochemistry for cytokeratin AE1/AE3 and vimentin V9. A canine mammary tumor was used for positive control. Agarose gel electrophoresis, PCR-ELISA and RT-PCR-ELISA were used to detect p53 and c-Myc genes. Results: The occurrence of p53 was detected in most of the eyelid tumors and third eyelid tumors studied (88.8%, n = 8) and was expressed in 75% of the positive samples, as indicated by ELISA. The c-Myc gene was found in 77.7% (n = 7) of the samples and was expressed in eight samples. Conclusions: Eyelid and third eyelid tumors of dogs express both the p53 and the c-Myc genes as shown by PCR and RT-PCR. However, PCR ELISA and RT-PCR ELISA were more efficient in assessing occurrence and expression of these genes because they identified amplified products that were not detected by agarose gel electrophoresis. © 2010 American College of Veterinary Ophthalmologists.
Keywords: C-Myc; Dog; ELISA; Eyelid tumors; P53; PCR; DNA; Myc protein; protein p53; RNA; animal; animal disease; dog; dog disease; eyelid tumor; gene expression regulation; genetics; metabolism; physiology; Animals; Dog Diseases; Dogs; Eyelid Neoplasms; Gene Expression Regulation, Neoplastic; Proto-Oncogene Proteins c-myc; Tumor Suppressor Protein p53; Canis familiaris